2007
DOI: 10.1163/156854107782024866
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature induces two growth-arrested stages and change of secondary metabolites in Bursaphelenchus xylophilus

Abstract: The third-stage dispersal juvenile (JIII) is the stage for survival and dispersal in the winter of the pine wood nematode, Bursaphelenchus xylophilus. Through investigations at different temperatures, we found two kinds of growth-arrested development, including the adult longevity extension and JIII formation induced by low temperature. They showed similar characters: densely packed lipid droplets and extended longevity. We considered that there were four stages in the formation of growth-arrested stages: indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…Tomminen et al (1991) showed that an extended duration (82 or 130 days) of exposing B. xylophilus populations to 3 or 12 caused the proportion of propagative juveniles to decrease from 40% to 10-20% and the proportion of third-stage dispersal juveniles to increase from 50% to 70-80%. Zhao et al (2007) suggested that B. xylophilus second-stage juveniles molted to third-stage dispersal juveniles at 4 , although the developmental zero point, the lower temperature of arrested development, of ca 10 estimated by Futai (1980) suggests the unlikely development of younger juveniles at 4 for B. xylophilus. In our experiment, there was an alternative, plausible explanation that a temporary raising of the temperature may have allowed the development of the nematodes to proceed at each sampling time.…”
Section: Resultsmentioning
confidence: 99%
“…Tomminen et al (1991) showed that an extended duration (82 or 130 days) of exposing B. xylophilus populations to 3 or 12 caused the proportion of propagative juveniles to decrease from 40% to 10-20% and the proportion of third-stage dispersal juveniles to increase from 50% to 70-80%. Zhao et al (2007) suggested that B. xylophilus second-stage juveniles molted to third-stage dispersal juveniles at 4 , although the developmental zero point, the lower temperature of arrested development, of ca 10 estimated by Futai (1980) suggests the unlikely development of younger juveniles at 4 for B. xylophilus. In our experiment, there was an alternative, plausible explanation that a temporary raising of the temperature may have allowed the development of the nematodes to proceed at each sampling time.…”
Section: Resultsmentioning
confidence: 99%
“…At present, some efforts have been made in the mechanism of low‐temperature resistance of PWN. The low‐temperature resistance process of PWN is so far known as widely regulated by complicated physiological, biochemical and molecular processes, which include some specific secondary metabolites [10], fatty acid metabolites [34], cGMP pathway [12] and patched‐related proteins [35]. However, to date, the mechanism of the low‐temperature resistance process of PWN remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, also stimulated by the decreased temperature, the second‐stage propagative juveniles gradually develop into specialized third‐stage dauer larva (DL 3 ). When the following spring comes, the fourth‐stage dauer larva, developed from specialized third‐stage dauer larva, is carried from one pine tree to another by the longhorn beetle, Monochamus alternatus [9–11]. Therefore, the ability of low‐temperature resistance is crucial for not only the survival but also the spread of this devastating pest.…”
mentioning
confidence: 99%
“…Nematode survival in wood with low moisture is known to occur and, as was observed in the current study, is partially achieved by a shift in the proportion of the population that enters the juvenile third stage larvae (J III ). This developmental stage is known for its resistance to temperature extremes, desiccation and food shortage, and therefore is adapted for surviving for considerable periods of time within dead trees (Ishibashi & Kondo, 1977; Mamiya, 1984; Kishi, 1995; Zhao et al. , 2007).…”
Section: Discussionmentioning
confidence: 99%